Cu(ii) complex-based fluorescence chemosensor for cyanide in aqueous media1. Issue 79 (28th August 2015) - Wang, Dan; Zheng, Jian-Quan; Yan, Xi; Zheng, Xiang-Jun; Jin, Lin-Pei
<x xml:space="preserve">Abstract</x> A Cu2+ complex-based fluorescence "off–on" chemosensor for the direct detection of CN− in the environment and in living cells was designed and prepared.